Molecular epidemiology and extended-spectrum β-lactamases production of klebsiella pneumoniae isolated from three dairy herds - Nóbrega, Diego B. [UNESP]; Guiduce, Marcos V. S. [UNESP]; Guimarães, Felipe F. [UNESP]; Riboli, Danilo F. [UNESP]; Cunha, Maria L. R. S. [UNESP]; Langoni, Hélio [UNESP]; Pantoja, José Carlos de Figueiredo [UNESP]; Lucheis, Simone Baldini [UNESP] (FapUNIFESP (SciELO), 2013)
The objectives of this study were to isolate Klebsiella pneumoniae from different sources in three dairy cattle herds, to use the pulsed-field gel electrophoresis (PFGE) to measure genotypic similarities between isolates within a dairy herd, to verify the production of extended- spectrum β-lactamases (ESBLs) by the double-disk synergy test (DDST), and to use the PCR to detect the main ESBLs subgroups genes. Three dairy farms were selected based on previous mastitis outbreaks caused by K. pneumoniae. Milk samples were collected from lactating cows and from the bulk tank. Swabs were performed in different locations, including milking parlors, waiting room, soil, animal's hind limbs and rectum. K. pneumoniae was isolated from 27 cases of intramammary infections (IMI) and from 41 swabs. For farm A isolates from IMI and bulk tank were considered of the same PGFE subtype. One isolate from a bulk tank, three from IMI cases and four from environmental samples were positive in the DDST test. All eight DDST positive isolates harbored the blashv gene, one harbored the blatem gene, and three harbored the blactx-m gene, including the bulk tank isolate. Our study confirms that ESBL producing bacteria is present in different locations in dairy farms, and may be responsible for IMI. The detection of ESBLs on dairy herds could be a major concern for both public and animal health.
Keywords: Dairy cattle herds; Extended-spectrum β-lactamases (ESBLs); Klebsiella pneumoniae; Pulsed-field gel electrophoresis (PFGE)